Хронобиологические особенности влияния экзогенного мелатонина на гормональную активность щитовидной железы у молодых крыс = Chronobiological features of the effect of exogenous melatonin on hormone thyroid activity in young rats - Gevorkyan, A. R. (Journal of Education, Health and Sport, 2016)
Gevorkyan A. R. Хронобиологические особенности влияния экзогенного мелатонина на гормональную активность щитовидной железы у молодых крыс = Chronobiological features of the effect of exogenous melatonin on hormone thyroid activity in young rats Journal of Education, Health and Sport. 2016;6(10):547-556. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.167878 http://ojs.ukw.edu.pl/index.php/johs/article/view/4010 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.10.2016. ХРОНОБИОЛОГИЧЕСКИЕ ОСОБЕННОСТИ ВЛИЯНИЯ ЭКЗОГЕННОГО МЕЛАТОНИНА НА ГОРМОНАЛЬНУЮ АКТИВНОСТЬ ЩИТОВИДНОЙ ЖЕЛЕЗЫ У МОЛОДЫХ КРЫС А. Р. Геворкян ГУ «Институт проблем эндокринной патологии им. В. Я. Данилевского HАМН Украины», г. Харьков Резюме У молодых самцов крыс популяции Wistar изучено влияние 10-дневных вечерних инъекций мелатонина в физиологическом диапазоне доз на функциональное состояние щитовидной железы с учетом ее активности в разное время суток. Показано, что курсовое введение мелатонина молодым крысам репродуктивного возраста с нормально функционирующими пинеальной и щитовидной железами вызывает дозозависимое снижение тиреоидных гормонов в крови как днем, так и ночью. Результаты данной работы доказывают антитиреоидный эффект экзогенного мелатонина в репродуктивном возрасте и указывают на то, что дополнительная мелатониновая терапия даже в физиологических дозах в молодом репродуктивном возрасте противопоказана. Ключевые слова: щитовидная железа, тиреоидные гормоны, мелатонин, суточные ритмы. CHRONOBIOLOGICAL FEATURES OF THE EFFECT OF EXOGENOUS MELATONIN ON HORMONE THYROID ACTIVITY IN YOUNG RATS A. R. Gevorkyan SI ”V. Danilevsky Institute of Endocrine Pathology Problems of the NAMS of Ukraine”, Kharkiv Abstract The effect of 10-day-long evening injection of melatonin in a physiological dose range on the functional state of the thyroid gland considering its activity at different times of the day was studied in young male Wistar rats population. It is shown that the course injection of melatonin to young rats of reproductive age with normal functioning of the pineal and thyroid causes the dose-dependent reduction of thyroid hormones in the blood of both day and night. The results of this study demonstrate the antithyroid effect of exogenous melatonin in the reproductive age and suggest that additional melatonin therapy, even at physiological doses in young reproductive age is contraindicated. Key words: thyroid gland, thyroid hormones, melatonin, circadian rhythms